Evaluation on Growth and Yield Attributes of Ten Winged Bean Accessions in the Guinea Savannah Zone of North Central Nigeria - Tswanya, M. N. (Advances in Social Sciences Research Journal, 2022)
Field experiment was conducted at the Biotechnology Advanced Research Centre Farm, Garki-Abuja during 2018 and 2019 cropping seasons to evaluate ten accessions of winged bean. The experiment was laid out using Randomized Complete Block Design (RCBD), replicated three times, respectively. Data collected on growth and yield parameters were number of leaves per plant, vine length per plant, number of flowers per plant, pod length per plant, number of seeds per plot, seed weight per plot and seed yield. These were subjected to analysis of variance (ANOVA) and significant means compared using Duncan Multiple Range Test (DMRT). Results obtained revealed that the growth parameters of the plants increased as the plant aged. The highest vine length was obtained from TPT 9 (102.77 cm) accession and least mean values were observed from TPT 30, TPT 33 and TPT 3 in ascending order (80.57cm, 81.43 cm and 81.73 cm). There was significant (p≤ 0.05) difference in seed yield among the accessions with the highest yield obtained from TPT 48 (4.54 t/ha) while the least mean value was gotten from TPT 19 (2.59 t/ha). From this study, it could be deduced that for optimum yield performance TPT 48 thrived better than other accessions and can therefore be adopted by farmers in this ecological zone.